Dimensioning of nursing staff in outpatient chemotherapy: application of the Workload Indicators of Staffing Need - Daniela Vivas dos Santos; Raquel Rapone Gaidzinski
ABSTRACT Objective: To apply the method developed by the World Health Organization, called Workload Indicators of Staffing Need for dimensioning the nursing staff for the care of cancer patients in a Chemotherapy outpatient clinic. Method: This is a quantitative, observational, documentary field study with an intentional sample. Prospective data were collected through the work sampling method. Results: Seventeen nurses and 12 nursing technicians participated in the study. A total of 3,727 observations were performed and were obtained the mean times and the relative working time of 23 nurses' interventions and 18 nursing technicians' interventions. The interventions corresponded to 88.5% of the relative working time of nurses and 83.9% of nursing technicians. Personal activities accounted for 8.2% of the relative working time of nurses and 7.9% of nursing technicians. The reliability test resulted in 86.3% concordance. Conclusion: The similarity between the staff required according to the method studied and the current staff showed that the Workload Indicators of Staffing Need has great potential and applicability for dimensioning nursing professionals safely.